Faktor yang Memengaruhi Waktu Tunggu Pelayanan Resep Rawat Jalan di Instalasi Farmasi Rumah Sakit: Sistematik Review - Made Karma Maha Wirajaya; Vitalia Fina Carla Rettobjaan (Jurnal Kesehatan, 2022)
Pharmacy services are one of the services that must be minimal in a hospital. One indicator to measure pharmaceutical services that meet standards is the waiting time for services, especially prescription drugs. Waiting time for services is one of the most important concerns because it affects patient satisfaction. The reality is that there are still waiting times for prescription drugs that do not meet the minimum service standards in hospitals. This research aims to determine the factors that influence waiting times for outpatient prescription services in hospital pharmacy installations. This study uses a descriptive approach. This study uses a systematic review. Several factors influence the waiting time for prescription drug services in hospital pharmacy installations, namely the lack of human resources in pharmaceutical installations, the completeness of patient files that have not been fulfilled, the lack of availability of drugs prescribed by doctors, the use of electronic and manual prescriptions together, the number of prescription doctors not in National Forum, the number of prescriptions that ask for concoction drugs, information systems in pharmaceutical installations that are less than optimal, doctors who are difficult to contact when prescriptions are difficult to read, space is inadequate. Hospitals need to pay attention to these factors so that they can maintain the quality of hospital services.